OMEGA - OSIRIS Mapping of Emission-line Galaxies in A901/2: I. Survey description, data analysis, and star formation and AGN activity in the highest density regions - Chies-Santos, A.L.; Rodriguez del Pino, B.; Aragón-Salamanca, A.; Bamford, S.P.; Gray, M.E.; Wolf, C.; Bohm, A.; Maltby, D.T.; Pintos-Castro, I.; Sanchez-Portal, M.; Weinzirl, T. (Oxford University Press, 2015)
We present an overview of and first results from the OMEGA (OSIRIS Mapping of Emission-line Galaxies in the multicluster system A901/2) survey. The ultimate goal of this project is to study star formation and active galactic nucleus (AGN) activity across a broad range of environments at a single redshift. Using the tuneable-filter mode of the Optical System for Imaging and low-Intermediate-Resolution Integrated Spectroscopy (OSIRIS) instrument on Gran Telescopio Canarias, we target Hα and [NII] emission lines over an ∼0.5×0.5 deg2 region containing the z∼0.167 multicluster system A901/2. In this paper, we describe the design of the survey, the observations and the data analysis techniques developed. We then present early results from two OSIRIS pointings centred on the cores of the A901a and A902 clusters. AGN and star-forming (SF) objects are identified using the [NII]/Hα versus WHα diagnostic diagram. The AGN hosts are brighter, more massive, and possess earlier type morphologies than SF galaxies. Both populations tend to be located towards the outskirts of the high-density regions we study. The typical Hα luminosity of these sources is significantly lower than that of field galaxies at similar redshifts, but greater than that found for A1689, a rich cluster at z∼0.2. The Hα luminosities of our objects translate into star formation rates (SFRs) between ∼0.02 and 6 Myr−1. Comparing the relationship between stellar mass and Hα-derived SFR with that found in the field indicates a suppression of star formation in the cores of the clusters. These findings agree with previous investigations of this multicluster structure, based on other star formation indicators, and demonstrate the power of tuneable filters for this kind of study.